2001
DOI: 10.1105/tpc.13.2.287
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking of Phosphatidylinositol 3-Phosphate from the trans-Golgi Network to the Lumen of the Central Vacuole in Plant Cells

Abstract: Very limited information is available on the role of phosphatidylinositol 3-phosphate (PI[3]P) in vesicle trafficking in plant cells. To investigate the role of PI(3)P during the vesicle trafficking in plant cells, we exploited the PI(3)P-specific binding property of the endosome binding domain (EBD) (amino acids 1257 to 1411) of human early endosome antigen 1, which is involved in endosome fusion. When expressed transiently in Arabidopsis protoplasts, a green fluorescent protein (GFP):EBD fusion protein exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
227
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 239 publications
(241 citation statements)
references
References 56 publications
12
227
0
1
Order By: Relevance
“…In yeast, protein transport to the vacuole depends on the Vam7 t-SNARE, and its targeting to the vacuole is dependent on PtdIns(3)P generation (Cheever et al, 2001). The role of PtdIns(3)P in vacuolar sorting has also been reported in plant cells (Matsuoka et al, 1995;Kim et al, 2001;Tse et al, 2004;daSilva et al, 2005;Oliviusson et al, 2006). Therefore, shortage of PtdIns(3)P may lead to failure in the recruitment and targeting of proteins necessary for vacuolar function, thus causing defects in vacuolar dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In yeast, protein transport to the vacuole depends on the Vam7 t-SNARE, and its targeting to the vacuole is dependent on PtdIns(3)P generation (Cheever et al, 2001). The role of PtdIns(3)P in vacuolar sorting has also been reported in plant cells (Matsuoka et al, 1995;Kim et al, 2001;Tse et al, 2004;daSilva et al, 2005;Oliviusson et al, 2006). Therefore, shortage of PtdIns(3)P may lead to failure in the recruitment and targeting of proteins necessary for vacuolar function, thus causing defects in vacuolar dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Since PtdIns(3)P is important for trafficking of vacuolar proteins in somatic plant cells (Matsuoka et al, 1995;Kim et al, 2001;Oliviusson et al, 2006), and because dynamic changes in vacuolar morphology is a prominent feature during pollen development (Yamamoto et al, 2003), we were curious whether the Table I. Segregation analysis of VPS34/vps34-1 and VPS34/vps34-2…”
Section: Pollen Grains From Vps34/vps34 Plants Are Defective In Vacuomentioning
confidence: 99%
See 1 more Smart Citation
“…Although type III PtdIns 3-kinase has also been identified in plant cells, its role has yet to be determined. It has been suggested that PtdIns(3)P is involved in intracellular vesicle trafficking by binding to the FYVE domain [11,21]. Bunney et al demonstrated that PtdIns 3-kinase is associated with active nuclear or nucleolar transcription sites, suggesting a role in the regulating transcription [27].…”
Section: Discussionmentioning
confidence: 99%
“…Arabidopsis protoplasts were isolated with an enzyme mixture containing 0.25% macerozyme R-10, 400 mM mannitol, 1 mM CaCl 2 and 5 mM MES-KOH (pH 5.6) and transfected by a polyethylene glycol-based method as previously described [21]. The viability of protoplasts was determined by staining with 1% Evans Blue.…”
Section: Transient Expression Of Ebd In Arabidopsis Protoplastsmentioning
confidence: 99%